2020
DOI: 10.1002/jctb.6639
|View full text |Cite
|
Sign up to set email alerts
|

Removal of NO by catalytic decomposition of vaporized H2O2 over Mo–Fe/TiO2 catalyst

Abstract: BACKGROUD A series of Mo–Fe/TiO2 catalysts were employed for the catalytic decomposition of vaporized H2O2 to remove nitric oxide in the low‐temperature range (80–160 °C). The experimental results and the physicochemical properties were evaluated using a variety of techniques. RESULTS The experiment results revealed that the 1.5%Mo–0.5%Fe/TiO2 catalyst exhibited the best catalytic activity and 97.6% NO removal efficiency was obtained at 80 °C. The formation of •OH radicals and oxygen vacancies was verified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Heterogeneous Fenton-like catalyst, in particular for flue gas treatment, can overcome the shortcomings of the traditional homogeneous Fenton system, such as pH restriction and accumulation of iron sludge. For example, Pu et al 18 employed a series of Mo-Fe/TiO 2 catalysts for the catalytic decomposition of vaporized H 2 O 2 to remove NO in the low-temperature range (80-160 °C). The experiment results revealed that the 1.5% Mo-0.5% Fe/TiO 2 catalyst exhibited the best catalytic activity, and 97.6% NO removal efficiency was obtained at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous Fenton-like catalyst, in particular for flue gas treatment, can overcome the shortcomings of the traditional homogeneous Fenton system, such as pH restriction and accumulation of iron sludge. For example, Pu et al 18 employed a series of Mo-Fe/TiO 2 catalysts for the catalytic decomposition of vaporized H 2 O 2 to remove NO in the low-temperature range (80-160 °C). The experiment results revealed that the 1.5% Mo-0.5% Fe/TiO 2 catalyst exhibited the best catalytic activity, and 97.6% NO removal efficiency was obtained at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction (SCR), which converts NO into N 2 with ammonia (NH 3 ) and precious metal catalysts at high temperature, represents the most mature technology in industrial denitrification. Nevertheless, the NO x concentration of post-SCR exhaust gas is struggling to meet increasingly strict regulations on emission of NO x . In addition, manufacturing NH 3 brings large energy consumption, and the conversion of NH 3 and NO to N 2 is not sustainable. , Recently, wet oxidation-absorption technologies have also been used for removing NO, where NO is oxidized by strong oxidants, like O 3 , H 2 O 2 , and Na 2 S 2 O 8 , and removed by basic absorbents. However, the oxidants and absorbents are not easily available and cannot be regenerated for the following denitrification processes, and the products are often low-value mixtures of nitrates and bases. More importantly, NO is the key intermediate for the synthesis of nitro chemicals, for example, millions of tonnes of HNO 3 are manufactured each year through the energy-demanding Ostwald process .…”
Section: Introductionmentioning
confidence: 99%